2004
DOI: 10.1080/09540120410001641066
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to antiretroviral therapy in rural persons living with HIV disease in the United States

Abstract: The current study delineated patterns and predictors of adherence to antiretroviral therapy in 329 persons living with HIV disease in rural areas of 12 US states. Participants provided self-report data on patterns of HIV medication adherence, reasons for missing medication doses, psychological symptomatology, life-stressor burden, social support, ways of coping, coping self-efficacy, the quality of their relationship with their main physician, and barriers to health care and social services. Based on adherence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
58
1
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(66 citation statements)
references
References 27 publications
6
58
1
1
Order By: Relevance
“…Medication adherence-Medication adherence was assessed using four-items adapted from previously validated measures (Catz, Kelly, Bogart, Benotsch, & McAuliffe, 2000;Chesney et al, 2000). Adherence difficulties were assessed based on a seven day recall period, consistent with other published reports (e.g., Heckman, Catz, Heckman, Miller, & Kalichman, 2004;Wilson, Tchetgen, & Spiegelman, 2001). Prior research confirms that a seven day assessment interval provides a valid estimate of adherence that correlates with electronic (MEMS) monitoring data and is predictive of viral load (Arnsten et al, 2001).…”
Section: Methodsmentioning
confidence: 94%
“…Medication adherence-Medication adherence was assessed using four-items adapted from previously validated measures (Catz, Kelly, Bogart, Benotsch, & McAuliffe, 2000;Chesney et al, 2000). Adherence difficulties were assessed based on a seven day recall period, consistent with other published reports (e.g., Heckman, Catz, Heckman, Miller, & Kalichman, 2004;Wilson, Tchetgen, & Spiegelman, 2001). Prior research confirms that a seven day assessment interval provides a valid estimate of adherence that correlates with electronic (MEMS) monitoring data and is predictive of viral load (Arnsten et al, 2001).…”
Section: Methodsmentioning
confidence: 94%
“…Las personas seropositivas al VIH que participaron en el presente estudio presentaron puntuaciones promedio intermedias en las preguntas relacionadas con el estrés y puntuaciones bajas en las relacionadas con la depresión, lo que indica que, en términos generales, este grupo de personas se ha ajustado favorablemente a su condición y a su tratamiento (22)(23)(24).…”
Section: Discussionunclassified
“…[8][9][10] While not all studies examining the relationship between alcohol use and medication adherence have found a negative association between the two, 11 some studies have determined that people consuming alcohol while undergoing ARV treatment prescribed are considerably less likely to be adherent to the medication. [12][13][14] Of especially great concern is the high prevalence of coinfection of HIV and hepatitis C virus (HCV), with the consequence that end-stage liver disease, accelerated as a result of alcohol use among those coinfected, has become a leading cause of illness and death among these individuals. 15,16 Furthermore, HCV treatment is less effective in people with HIV=HCV coinfection, and its effectiveness is limited even more by ongoing alcohol use.…”
Section: Introductionmentioning
confidence: 99%